The Anti-Angiogenic Activity of Phoenix Dactylifera Seeds Methanol Extract in Vivo Study: Phoenix dactylifera seeds Methanol Extract in vivo study - Hussein, Zeena A; Al-Zubaidy, Adeeb A; Sahib, Hayder B (Iranian Journal of Pharmaceutical Sciences, 2018)
The aim of the study was to identify the antiangiogenic activity of Phoenix dactylifera seeds methanolic extract in vivo and the probable anti-angiogenic mechanism of action. The date seeds were extracted with methanol using cold method, the crude extract was tested on chick chorioallantoic membrane (CAM) as an in vivo anti-angiogenic assay. Fourier transform infrared spectroscopy FT-IR was carried to identify the functional group for the active chemical constituents. The results demonstrated significant inhibition of blood vessels growth, and FTIR showed the presence of different functional group such as OH, NH2 and phenols. From the data above the mechanism of action may relate to the presence of flavonoids and other phenolic compounds, as they have direct perturbing action on blood vessels and prevent cell proliferation of endothelial cells growth via their potent antioxidant and anti-inflammatory effects.